ANALISIS PEMBIAYAAN DENGAN PRINSIP MURABAHAH PADA PT. BANK SUMUT SYARIAH CABANG MEDAN - Fitriyani Panjaitan; Andri Soemitra (MANAJEMEN, 2021)
This study discusses the analysis of financing with the principle of murabahah at PT. Bank Sumut Syariah Medan. The murabahah contract is the sale and purchase of goods at the original price with an additional profit agreed upon by the seller, who must notify the price of the product he purchased and determine a level of profit in addition to it. The research method used is descriptive qualitative with data collection techniques through interviews and observations. The results showed that the murabahah financing mechanism at Bank Sumut Syariah Brigjen Katamso Medan can be used by all human beings where the type of business must remain in accordance with Islamic sharia and in order to minimize the risk of default the bank provides action in the form of supervision.